Soil-saving Agricultural Technologies and State Support for Socially vulnerable segments of the Population in preventing Poverty - Victor F. STUKACH (Communications of International Proceedings, 2020)
The article deals with a problem of high political and social significance: providing environmentally friendly food to socially vulnerable categories of the population. This category includes pregnant and nursing women, children, school children, clients of social institutions, and segments of the population whose real incomes are below the subsistence level. The amount of food consumed by this category of population can be 17-20% of the volume in the region. We need land resources that can be used to produce organic food without the use of pesticides with a limited amount of fertilizers. Goal. To investigate the problem of providing environmentally friendly food to socially unprotected categories of the population. Consider mechanisms for coordinating market, distribution, and informal institutions to provide food to socially vulnerable segments of the population. It is proposed to use state support tools to encourage land users to use soil protection technologies, introduce degraded land into agricultural circulation, and create food aid infrastructure in the regions. It is proposed to use state support tools to ensure the use of soil-protecting agricultural technologies, to create a system of food aid to overcome the poverty of socially vulnerable segments of the population.
Keywords: degraded land; soil protection technologies; state support; poverty prevention; infrastructure of domestic food aid in the region.